2015
DOI: 10.1177/1938640015585963
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Foot Self-Care in Patients With Diabetes

Abstract: Therapeutic, Level III: Systematic review of level I-III studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…Of all the variables included in the model, we observed that “low educational level” increases the risk of losing protective sensitivity (OR: 31.4, 95% CI: 2.5‐383.3, P = .007); however, the confidence interval is quite high, so the risk—although present—may be overestimated by the sample size. Those with a lower level of education typically have poorer health habits, causing increased obesity, physical inactivity, and susceptibility to psychosocial risks, which increases the risk of suffering from neuropathy . Therefore, it is important to establish preventative programs aimed at less educated populations to reduce the prevalence of PN.…”
Section: Discussionmentioning
confidence: 99%
“…Of all the variables included in the model, we observed that “low educational level” increases the risk of losing protective sensitivity (OR: 31.4, 95% CI: 2.5‐383.3, P = .007); however, the confidence interval is quite high, so the risk—although present—may be overestimated by the sample size. Those with a lower level of education typically have poorer health habits, causing increased obesity, physical inactivity, and susceptibility to psychosocial risks, which increases the risk of suffering from neuropathy . Therefore, it is important to establish preventative programs aimed at less educated populations to reduce the prevalence of PN.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the SDFQ reflects awareness of diabetic foot self-care in study subjects, and it can also be used to evaluate the post-interventional differences to determine the state of foot health within the population. 17,19,38 The main purpose of the research is the measurement of diabetic foot self-care population using a questionnaire, adapted to the Italian language the SDFQ as a valid measure. 13…”
Section: Key Messagesmentioning
confidence: 99%
“…Diabetic foot self‐care must be a daily routine, patients must develop this habit from the beginning of diabetic symptoms such as a right administration of the chronic process. 15 It has been estimated that self‐care conduct on diabetic subjects is one of the main aspects to take the control of basic pathology. The self‐efficacy model has important results related to self planification about benefits conduct.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Although most patients with diabetic peripheral neuropathy experience no pain, approximately 11% of patients have chronic, painful symptoms which decrease their quality of life, disrupt sleep, and can lead to depression. 3,4 Painful diabetic neuropathy can significantly impair patients' quality of life 3 and affect many areas of everyday life. [5][6][7] The number of amputations is growing due to the increasing incidence of diabetes and vascular disease, as well as due to population aging.…”
Section: Introductionmentioning
confidence: 99%